The Biology of Hover Wasps - Turillazzi, Stefano; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book represents the culmination of the author$1 (Bs lifetime work on a single fascinating group of insects, the hover wasps, Stenogastrinae. The author explores the biology of these little-known wasps at the threshold of sociality, presenting an ambitious survey of ideas about their evolution and an assessment of the current standing of controversial concepts. Following taxonomic and morphological descriptions, the behaviour, colonial dynamics, social communication and especially the remarkably diverse nests of wasps are discussed. Compared to the better-known species of paper wasps, hornets and yellowjackets, the hover wasps show various peculiarities, such as characteristics of immature brood rearing, nest defence and mating systems. The nest architecture probably presents the most variable solutions in social wasps and is characterized by an astonishing level of camouflage, making these insects an interesting example of special adaptation to forest environments.s
The Hover Wasps -- Morphology and Anatomy -- Behaviour -- Colonial Dynamics -- Social Communication -- The Nest of Hover Wasps -- The Evolution of Social Behaviour in Insects and the Hover Wasps.
Keywords: Life sciences; Animal behavior; Evolution (Biology).; Zoology; Entomology; Life Sciences; Entomology; Behavioural Sciences; Evolutionary Biology; Zoology